The efficacy and safety of post-stroke cognitive impairment therapies: an umbrella review - Li, Yongbiao; Cui, Ruyi; Liu, Shaobo; Qin, Zhiping; Sun, Wenjing; Cheng, Yong; Liu, Qingshan (Frontiers in Pharmacology, 2023)
Background: Stroke survivors are at significantly increased risk of cognitive impairment, which affect patients' independence of Activities of daily living(ADL), social engagement, and neurological function deficit. Many studies have been done to evaluate the efficacy and safety of Post-stroke cognitive impairment (PSCI) treatment, and due to the largely inconsistent clinical data, there is a need to summarize and analyze the published clinical research data in this area.Objective: An umbrella review was performed to evaluate the efficacy and safety of PSCI therapies.Methods: Three independent authors search for meta-analyses and systematic reviews on PubMed, the Cochrane Library and Web of Science to address this issue. We examined ADL and Barthel index (BI), Montreal Cognitive Assessment(MoCA), neurological function deficit as efficacy endpoints, and the incidence of adverse events as safety profiles.Results: Nineteen eligible papers including 312 studies, were included in the umbrella review. The results showed that angiotensin-converting enzyme inhibitors (ACEI) inhibitors and N-methyl-D-aspartate (NMDA) antagonists, cell therapies, Acupuncture, EGB76 can improve the MoCA and ADL, and the adverse effects were mild for the treatment of PSCI. Moreover, Vinpocetine, Oxiracetam, Citicoline, thrombolytic therapy, Actovegin, DL-3-n-Butylphthalide, Nimodipine showed adverse events or low article quality in PSCI patients, Research evidence is not exact, and further research is needed.Our study demonstrated that ACEI inhibitors(Donepezil) and NMDA antagonists(Memantine), EGB761, Acupuncture are the ADL and BI, MoCA and neurological function deficit medication for patients with PSCI.